Morphological and phylogenetic characteristics of Phaeomycocentrospora xinjangensis (Pleosporales, Dothideomycetes), a new species from China - Ren, Yu-Lian; Zhang, Zhi-Yuan; Chen, Wan-Hao; Liang, Jiang-Dong; Han, Yan-Feng; Liang, Zong-Qi (Phytotaxa, 2022)
The genus Phaeomycocentrospora (Dothidotthiaceae) is a fungal pathogen causing plant leaf spots. A new species, Phaeomycocentrospora xinjangensis sp. nov. is introduced from Xinjiang Uygur Autonomous Region, Northwest China. Multi-gene phylogenetic analyses based on a concatenated ITS, LSU, and ACT sequence dataset were used to confirm the phylogenetic position of the new species. Phaeomycocentrospora xinjangensis can easily be distinguished from the remaining species based on multi-gene phylogenetic analyses coupled with morphological characters. Morphologically, P. xinjangensis differs from other species in the genus by the presence of dark hyphae, dark brown conidiophores, few branched conidiogenous cells. Phylogenetically, our three strains were clustered together and formed a separate subclade with high support values. Moreover, we provided a description, illustrations, and phylogenetic tree for the new species.